2008
DOI: 10.1021/jm700940h
|View full text |Cite
|
Sign up to set email alerts
|

Meriolins (3-(Pyrimidin-4-yl)-7-azaindoles): Synthesis, Kinase Inhibitory Activity, Cellular Effects, and Structure of a CDK2/Cyclin A/Meriolin Complex

Abstract: We report the synthesis and biological characterization of 3-(pyrimidin-4-yl)-7-azaindoles (meriolins), a chemical hybrid between the natural products meridianins and variolins, derived from marine organisms. Meriolins display potent inhibitory activities toward cyclin-dependent kinases (CDKs) and, to a lesser extent, other kinases (GSK-3, DYRK1A). The crystal structures of 1e (meriolin 5) and variolin B (Bettayeb, K.; Tirado, O. M.; Marionneau-Lambert, S.; Ferandin, Y.; Lozach, O.; Morris, J.; Mateo-Lozano, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
136
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(142 citation statements)
references
References 87 publications
4
136
0
2
Order By: Relevance
“…Table 3, and significant antiproliferative effects were observed in various cancer cell lines, likely due to inhibition of multiple cell cycle kinases targets. 81 No reports have been found detailing the activity of these molecules in DYRK1A cellular phosphorylation assays, which may represent an opportunity for further study.…”
mentioning
confidence: 99%
“…Table 3, and significant antiproliferative effects were observed in various cancer cell lines, likely due to inhibition of multiple cell cycle kinases targets. 81 No reports have been found detailing the activity of these molecules in DYRK1A cellular phosphorylation assays, which may represent an opportunity for further study.…”
mentioning
confidence: 99%
“…Taxotere was used as a positive control at a drug concentration of 2.5 × 10 −10 M with 46% of HL60 cell growth inhibition and 32% of K562 cell growth inhibition. In vitro kinase inhibitory potencies of compounds 3-7, 10, 11, 13-15 were evaluated toward CDK5/p25, GSK3, CK1 and DyrK1A as already described in the literature [11] by Laurent Meijer's group (Station Biologique CNRS, Roscoff, France). Regarding the residual kinase activity (more than 65%) when the compounds were tested at 10 µM, none of them was particularly active toward these kinases.…”
Section: Resultsmentioning
confidence: 99%
“…32) Echalier et al 33) reported successful design of CDK inhibitors using interactions with the ribose binding region. Meriolins, structural hybrid of two natural kinase inhibitors (meridianins and variolins), are highly potent inhibitors of CDKs.…”
Section: Interactions Of 7-azaindole-based Inhibitors With Adjacent Bmentioning
confidence: 99%